In Search of Indigenous Wisdom and Interdisciplinary Ways of Learning Together. Issue 3 (3rd July 2018) - Haines, Jelina; Du, Jia Tina; Trevorrow, Ellen
ABSTRACT: Advances in technology have transformed our daily life communication activities. These days, online communication has become a norm and universally follows patterns of mass information sharing. In the Indigenous context, the community is inundated with the sheer volume of data available online. Thus, the capability of retrieving Elders' knowledge relies on access to modern technology and the competency of end users. These issues may pose a challenge to the library and information services sector (LIS), as well as for Indigenous Elders who may have limited access to present technologies. This article synthesises the importance of understanding the Indigenous wisdom in engaging with Aboriginal people while emphasising the reciprocated relationship as opposed to a partnership approach. The authors drew on the value of Elders stories and shared learning practices expressed in the findings. Video dialogue process of unstructured interview was employed using visual ethnographic approach within the Community-Based Participatory Research (CBPR) paradigm. Data collected from three prominent Elders. Video recording had provided research participants with a voice adding rigour and accuracy to the information gathered, as contrasting to traditional observations. The video recording has led to approaches to work for and with Indigenous people ethically comprising valuable information significant to LIS. Abbreviations : Community-Based Participatory Research (CBPR), Library and Information Sciences (LIS), Conversational Analysis (CA)